ENHANCING GOVERNMENT’S SPBE CHANGE MANAGEMENT UTILIZING STRATEGIC COMMUNICATION - Putuasduki, Eka Putra Mahardika; Putri, Erita (Departemen Komunikasi dan Penyiaran Islam, 2024)
This research delves into examining the significance of strategic communication in bolstering change management within the framework of Sistem Pemerintahan Berbasis Elektronik (SPBE) in Indonesia. Through the utilization of qualitative research methodologies, encompassing descriptive analysis and an exhaustive review of existing literature, the study seeks to pinpoint the pivotal factors that influence the effectiveness of SPBE endeavors. The results highlight that well-structured communication tactics, dedication from leadership, and active involvement of employees are crucial in mitigating resistance and harmonizing organizational aims with SPBE objectives. Moreover, the amalgamation of established change management models, such as ITIL v4 and ISO/IEC 20000, with SPBE directives, markedly enhances the efficiency of digital transformation projects. Additionally, the study recognizes prevalent obstacles, like insufficient infrastructure and disjointed coordination, and recommends the implementation of continual enhancements and flexible strategies to tackle these challenges. Lastly, the research puts forth suggestions for formulating specific SPBE change management protocols and advocates for further investigations into the effects of diverse communication approaches in different governmental settings.